One-dimensional metal oxide nanostructures for heterogeneous catalysis - Zhang, Qian (2015)
Metal oxides are of paramount importance in heterogeneous catalysis as either supports or active phases. Controlled synthesis of metal oxide nanostructures has received enormous attention in heterogeneous catalysis due to the possibility of tailoring the properties of metal oxides by tuning their shapes, sizes, and compositions. For instance, through the well-defined nanocrystals, the catalytic activity and selectivity can be enhanced by selectively exposing a specific facet. The research work presented in this thesis focuses on the synthesis of novel metal oxide with one-dimensional nanostructures, including TiO2, MnO2 and CuO, and their applications as catalytic materials for a series of selective oxidation reactions, with the aim of introducing new insights into the heterogeneous catalyst design.